MECHANISM FOR ASSESSING THE QUALITY OF TEACHING IN A HYBRID LEARNING FORMAT - Садирбекова, Динара; KIKBANOVA, A.; NISHANBAYEVA, S. (Pedagogy and Psychology, 2024)
The article is devoted to the analysis of the theoretical provisions of pedagogical research on mechanisms for assessing the quality of teaching in a hybrid learning format. The purpose of this study is to describe the features of methodological approaches to assessing the quality of teaching in a hybrid learning format in relation to the educational process in higher education. Research methods: The assessment of the quality of teaching was determined by the assessment of the quality of educational technologies (content of lectures and practical classes). Through the structure of evaluation of educational results as the quality of learning of students in the curriculum. How to evaluate the quality of education: subjective self-evaluation of teachers and objective evaluation of students through surveys and questionnaires. The resulting research results made it possible to demonstrate the theoretical and methodological basis for modeling the university’s hybrid educational environment. It became clear that the main provisions of the analysis and determination of the quality of education are the constancy of the signs of the quality of education and the component composition of the professional activity of the teacher in the university. The level assessment of the expression of each quality attribute in the analysis of educational activity is determined. The structure of educational evaluation is represented regardless of the details of the subject and the content of the discipline. Indicators for assessing the quality of education in an organized, hybrid learning format include immutability, monitoring, intercommunication, polymorphism, self-deviation, personalization, feedback, etc.